Antihypertensive effect and lethal dose 50 of Passiflora edulis leaves (maracuya) fruit juice and ethanolic extract in rats - Rojas, Juan (2006)
Objetives: To determine the antihypertensive effect and lethal dose (LD) 50 of the fruit juice and ethanolic extract from Passiflora edulis leaves in rats. Design: Prospective, analytic-experimental, preclinical in vivo study. Setting: Faculties of Medicine, Chemistry and Chemical Engineering and Pharmacy and Biochemistry, San Marcos National University. Biologic material: Rats. Interventions: Four groups of rats (n = 6) were used to determine the antihypertensive effect. After basal determination, arterial hypertension was induced using L-NAME 50 mg/kd/d VO and two days later the treatment was initiated with distilled water, ethanolic extract (500 mg/kg/d) VO, fruit juice 500 mg/kg/d VO, captopril 100 mg/kg/d VO, respectively. Arterial pressure was measured on days 3, 4, 7 and 10. For determining LD50, 12 groups of mice (n=10) were used with 7 different dose levels of ethanolic extract, and 5 levels for the one dose juice. Main outcome measures: Blood pressure decrease. Results: The ethanolic extract and the fruit juice decreased the systolic blood pressure (SBP) starting the first day of treatment: 157,2 ± 2,3 and 156,2 ± 2,1 mmHg compared to 167,7 ± 1,7 mmHg of the L-NAME group (p < 0,005 y p < 0,001), respectively. Also the diastolic blood pressure (DBP) significantly decreased starting the first day of treatment. LD50 for the ethanolic extract and juice fruit were 10 687 and 21 471 mmHg, respectively. Conclusions: Ethanolic extract of the leaves and the fruit juice of Passiflora edulis were effective to decrease the arterial blood pressure in hypertensive rats, without oral acute toxicity.